Analysis of the Study of Digital Marketing Potential on Product Purchase Decisions in Generation Z - Ayu Alfyya Fathinasari; Purnomo, Hery; Poniran Yudho Leksono (HM Publisher, 2023)
Generation Z grew up with easy access to the internet. They tend to spend more time online than previous generations. This opens up great opportunities for sellers to reach them through various digital platforms. This study aimed to conduct an analysis of the study of the potential of digital marketing for product purchasing decisions in generation Z. This research is qualitative research that explores and describes in detail a situation or phenomenon of the research object studied by developing concepts and gathering existing facts. Platforms like Facebook, Instagram, Twitter, LinkedIn, and Snapchat are popular channels for digital marketing. Sellers can share content, conduct paid advertising campaigns, interact with users, and build relationships with audiences through social media. Company websites and blogs are the main channels in digital marketing. Sellers can create informative content, describe products or services, provide special offers, and drive traffic to their websites through SEO (search engine optimization) strategies and online advertising campaigns. Email is an effective channel for sending direct sales messages to audiences. Sellers can collect email addresses of customers or prospects and send them personalized content, special offers, product updates, or newsletters on a regular basis. Search engine marketing (SEM) includes the use of paid advertising on search engines such as Google Ads. Sellers can display their ads on search results pages or on partner websites relevant to their targeted keywords. Platforms like YouTube, TikTok, and Vimeo are popular channels for video content. Merchants can create promotional videos, product reviews, tutorials, or entertaining content to reach a wider audience.